Screening and Confirmation of Vip3 gene presence in Bacillus thuringiensis strains native to Nepal - Dahal, Sagar; Sijapati, Jaishree; Rijal, Sandeep (International Journal of Applied Sciences and Biotechnology, 2022)
An insecticidal protein named Vegetative Insecticidal Protein (Vip) produced by Bacillus thuringiensis during its vegetative growth is gaining its popularity as second-generation insecticidal protein because of its lethal effect on insects of class Coleoptera, Lepidoptera, Diptera. The research was designed for the confirmation of Vip3 gene presence in soil samples collected from different geographical region of Nepal. For the purpose, 36 soil samples from different places of Nepal were collected. Primers were used for PCR amplification of DNA templates extracted and product size was observed around 1621bp.Out of total sample analyzed, 10% of sample showed the presence of Vip3 gene. Int. J. Appl. Sci. Biotechnol. Vol 10(1): 71-74.